Algebra Problem with 0

Jason76

Senior Member
Joined
Oct 19, 2012
Messages
1,180
\(\displaystyle 12x^{2} - 64 = 0\)

\(\displaystyle x^{2} = \dfrac{64}{12}\)

\(\displaystyle x = \pm \dfrac{64}{12}\)

\(\displaystyle x = \pm \dfrac{16}{3}\) :confused:
 
Last edited:
\(\displaystyle 12x^{2} - 64 = 0\)

\(\displaystyle x^{2} = \dfrac{64}{12}\)

\(\displaystyle x = \pm \dfrac{64}{12}\)
How did you get that the square root of 64/12 was 64/12? Are you familiar with "square roots" at all?
 
\(\displaystyle 12x^{2} - 64 = 0\)

\(\displaystyle x^{2} = \dfrac{64}{12}\)

\(\displaystyle x^{2} = \dfrac{16}{3}\)

\(\displaystyle x = \pm \sqrt{\dfrac{16}{3}}\)
 
\(\displaystyle 12x^{2} - 64 = 0\)

\(\displaystyle x^{2} = \dfrac{64}{12}\)

\(\displaystyle x^{2} = \dfrac{16}{3}\)

\(\displaystyle x = \pm \sqrt{\dfrac{16}{3}}\)
Now rationalize the denominator. ;)
 
Top